Usus al-amn al-fikri fi al-sunnah al-nabawiyah (Basics of security thinking in prophets sunnah) - Badi, Jamal Ahmed Bashier; Ahmed Shogar, Ibrahim Adam (Academic Publication Council, Kuwait University, 2011)
Security thinking has become one of the necessities of preserving the basics, principles and value of Islamic Civil culture confronting current challenges risks. The most important one is globalization. In this paper we try to introduce an Islamic vision establishing basics of thinking security in its comprehensive concept and wide significance coming up from the Sunnah of our Prophet Mohamed (peace be upon him) by employing what was mentioned in the Sunnah of origins and applications it can be a guiding light for generations of our ascending Ummah. They keep following its guiding principles. The Ummah recognize clearly the ways of being pioneers in civilization. This paper attempts answering the following questions :